A comprehensive analysis of failure of cross bearing of universal spindle in Hot Strip Mill. (April 2019) - Patel, Subodh Nath; Palit, Piyas; Mishra, Alok; Mathur, Jitendra; Bhattacharyya, Sandip
Abstract: Universal spindle of Finishing Stand in Hot Strip Mill (HSM) plays a vital role in providing product thickness as per customer requirement. In a rolling mill, upper and lower work rolls are connected with single motor by their respective universal spindle. The spindle allows upward and downward movement of work rolls by allowing its shaft to bend up to ~15 o angle. This bending is only possible by universal cross positioned at its both ends. One of the cross bearing located at operator side got failed during operation. All the site evidences were carefully noted down and piled up to find out the root cause of the failure. Metallurgical analysis like microstructure, hardness, inclusion rating and chemical analysis were carried to find out material related issue if any. Quality of lubricants used at different pins of cross bearing was also checked by crackle test. Evidences and metallurgical analysis results suggested that the cross bearing failed due to deterioration of lubricant quality during service. Lubricant deteriorated due to water ingress into cross bearing through its polymeric seal which was not properly applied at the time of its assembly. Highlights: Cross bearing of universal spindle of Hot Strip Mill failed in service. Pits and deformation were observed on different elements of failed cross bearing. From the visual and metallurgical inspection, it was concluded that pitting had no role in failure. It occurred after failure. Bearing failed due to water ingress into the bearing due to breakage of sealant.